2018
DOI: 10.1371/journal.pone.0196177
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cortical participation during bilateral, cyclical ankle movements: Effects of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is known to increase asymmetry and variability of bilateral movements. However, the mechanisms of such abnormalities are not fully understood. Here, we aimed to investigate whether kinematic abnormalities are related to cortical participation during bilateral, cyclical ankle movements, which required i) maintenance of a specific frequency and ii) bilateral coordination of the lower limbs in an anti-phasic manner. We analyzed electroencephalographic and electromyographic signals from ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…For instance, Salenius et al (2002) reported a levodopa effect on beta corticomuscular coherence during isometric forearm contractions, while Pollok (2012) and Hirschmann (2013) did not. Notably, Yoshida et al (2017Yoshida et al ( , 2018 found decreased corticomuscular coherence in older people compared to young adults during rhythmic ankle movements but not between older and PD participants (similar to our results) when tested their PD participants in an 'off-medication state' (after overnight withdrawal). This creates uncertainty with regards to potential medication effects on cortical and corticospinal oscillatory activity during walking in people with PD, and it is possible that we did not find differences between the PD and age-matched control group because the PD group was assessed in an on-medication state.…”
Section: Limitationssupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, Salenius et al (2002) reported a levodopa effect on beta corticomuscular coherence during isometric forearm contractions, while Pollok (2012) and Hirschmann (2013) did not. Notably, Yoshida et al (2017Yoshida et al ( , 2018 found decreased corticomuscular coherence in older people compared to young adults during rhythmic ankle movements but not between older and PD participants (similar to our results) when tested their PD participants in an 'off-medication state' (after overnight withdrawal). This creates uncertainty with regards to potential medication effects on cortical and corticospinal oscillatory activity during walking in people with PD, and it is possible that we did not find differences between the PD and age-matched control group because the PD group was assessed in an on-medication state.…”
Section: Limitationssupporting
confidence: 85%
“…Changes in corticomuscular coherence with ageing and PD has not yet been investigated during walking, but a few studies have investigated it in other tasks. During cyclical ankle movements -as a simulation of rhythmic natural walking -corticomuscular coherence was reduced in older compared to young participants (Yoshida et al 2017), but it was not different between people with PD and age-matched controls even though movement performance varied between these groups (Yoshida et al 2018). Notably, beta-band coherence was enhanced in older compared to young participants during abduction of the index finger (Johnson & Shinohara 2012), although others reported it reduced during elbow flexion (Graziadio et al 2010, Bayram et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also examined corticomuscular coherence during walking and cycling in PD (Yoshida et al, 2018;Gunther et al, 2019;Roeder et al, 2020). Subjects with PD and older age-matched participants did not show significant differences in corticomuscular coherence during double support phase in walking, nor bilateral cycling (Yoshida et al, 2018;Roeder et al, 2020). Together, these studies suggest abnormal cortical oscillations in PD does not affect the direct corticospinal drive to muscles during walking, but may impair walking via other indirect pathways (e.g., corticalbasal ganglia loop, cortico-brainstem).…”
Section: Cortical Oscillations During Gaitmentioning
confidence: 89%
“…This suggests that increased oscillatory synchronization in the both cerebral cortex and basal ganglia are associated with clinical features of gait disorders in PD. Several studies have also examined corticomuscular coherence during walking and cycling in PD (Yoshida et al, 2018;Gunther et al, 2019;Roeder et al, 2020). Subjects with PD and older age-matched participants did not show significant differences in corticomuscular coherence during double support phase in walking, nor bilateral cycling (Yoshida et al, 2018;Roeder et al, 2020).…”
Section: Cortical Oscillations During Gaitmentioning
confidence: 99%
“…Changes in corticomuscular coherence with ageing and PD has not yet been investigated during walking, but a few studies have investigated it in other tasks. During cyclical ankle movements -as a simulation of rhythmic natural walking -corticomuscular coherence was reduced in older compared to young participants 82 , but it was not different between people with PD and age-matched controls even though movement performance varied between these groups 83 . Notably, beta-band coherence was enhanced in older compared to young participants during abduction of the index finger 84 , although others reported it reduced during elbow flexion 85,86 .…”
mentioning
confidence: 89%